Clinical risk scores for predicting stroke-associated pneumonia: A systematic review. (June 2016) - Kishore, Amit K; Vail, Andy; Bray, Benjamin D; Chamorro, Angel; Napoli, Mario Di; Kalra, Lalit; Langhorne, Peter; Montaner, Joan; Roffe, Christine; Rudd, Anthony G; Tyrrell, Pippa J; de Beek, Diederik van; et al.
Purpose: Several risk stratification scores for predicting stroke-associated pneumonia have been derived. We aimed to evaluate the performance and clinical usefulness of such scores for predicting stroke-associated pneumonia. Method: A systematic literature review was undertaken in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement, with application of the Quality Assessment of Diagnostic Accuracy-2 tool. Published studies of hospitalised adults with ischaemic stroke, intracerebral haemorrhage, or both, which derived and validated an integer-based clinical risk score, or externally validated an existing score to predict occurrence of stroke-associated pneumonia, were considered and independently screened for inclusion by two reviewers. Findings: We identified nine scores, from eight derivation cohorts. Age was a component of all scores, and the NIHSS score in all except one. Six scores were internally validated and five scores were externally validated. The A2DS2 score (Age, Atrial fibrillation, Dysphagia, Severity [NIHSS], Sex) was the most externally validated in 8 independent cohorts. Performance measures were reported for eight scores. Discrimination tended to be more variable in the external validation cohorts (C statistic 0.67–0.83) than the derivation cohorts (C statistic 0.74–0.85). Discussion: Overall, discrimination and calibration were similar between the different scores. No study evaluated influence on clinical decision making or prognosis. Conclusion: The clinical prediction scores varied in their simplicity of use and were comparable in performance. Utility of such scores for preventive intervention trials and in clinical practice remains uncertain and requires further study.